(Re-)Imagining the Caméra-Stylo in a Contemporary Screen Culture of Social Media and Smartphone Mobilography - Murphy, Cáit (Trinity College Dublin. School of Creative Arts. Discipline of Film, 2026)
In 1948, French film critic Alexandre Astruc published two essays, 'The Birth of a New Avant-Garde: La Caméra-Stylo' and 'The Future of Cinema', in which he proposed his most famous formula of the 'caméra-stylo'/'camera-pen'. For cinema to truly become an art form, according to Astruc, it needed to be articulated as subtly and personally as a writer writes with a pen in their hand. The 'camera-pen' imagines self-expression in audiovisual terms and would help give rise to notions of the auteur director in French film criticism in the 1950s. However, Astruc also noted the rise of television and 16mm as screen technologies that could be handled, accessed, and viewed by the masses in their own homes and in the streets. His vision of future screen media expanded far beyond the film industry and the film theatre. This thesis resituates Astruc's vision in contemporary digital screen culture. Today, smartphones and social media platforms as tools for the creation and dissemination of screen media have revolutionised personal screen production for the masses. Mobile filmmaking -- what I term 'mobilography' (mobile writing) -- has become the mark of a screen culture where cameras are always at-hand. I ask how has the caméra-stylo been realised and re-imagined in contemporary digital screen culture, in a screenscape where 'auteur' filmmakers and the broader public use smartphones and social media for the creation and dissemination of personal screen media? Scholars such as Laura Rascaroli, Bjørn Sørenssen, and Christian Keathley have noted how Astruc's theory finds resonance in practices such as smartphone filmmaking, YouTube vlogging, and videographic criticism. But scholarship on the caméra-stylo has yet to analyse new technologies like TikTok and generative AI as well as non-Western voices -- a shortcoming addressed by this thesis. Informed by debates on the 'death' of cinema in the digital age, media archaeology, and concepts like 'post-cinema' and intermediality, my thesis aims to novelly coalesce studies on social media aesthetics and practices with Astruc's and related theories, offering the first major study on this topic. Using a case study approach and close textual analysis, I identify key instances where Astruc's vision is realised and re-imagined today, from auteur films to the mobilography of ordinary social media users. I firstly theorise four key aspects of the caméra-stylo and contemporary digital screen culture that inform subsequent chapters: auteurism and authorship, the new avant-garde, mobilography, and hands, hapticity, and bodies. I find that the caméra-stylo has been re-imagined in contemporary auteur films that formally integrate the aesthetics of amateur smartphone footage and content creators, in case studies from Happy End (Michael Haneke, 2017) to Do Not Expect Too Much from the End of the World (Radu Jude, 2023). I also show that auteurs have personally adopted social media as informal extensions of their caméra-stylo and subjective embodiment, with case studies on Nicolas Winding Refn's and Claire Denis's Instagram profiles. I also demonstrate that the caméra-stylo has been re-imagined by fans in the digital age who co-creatively engage with auteurism, by analysing a case study on Wes Anderson fan media, including the viral 2023 TikTok trend and AI-generated media. I finally consider the caméra-stylo in global struggles, looking at a case study on Palestinian activist mobilographers' videos on Instagram, thus broadening Astruc's vision to include non-Western, marginalised voices. This thesis significantly informs our theoretical understanding of Astruc's 'old' film theory in the digital age, by showing the multiple aesthetic and historical connections between cinema and new media. This thesis contributes to new understandings of Astruc's concept by expanding its application to new technologies, aesthetics, and practices outside of the film industry.
APPROVED
Keywords: camra-stylo; social media; camera-pen; film studies; screen studies; smartphone; auteur theory; Instagram; Claire Denis; activism; Nicolas Winding Refn; Wes Anderson; TikTok; Generative artificial intelligence; mobilographer; digital media; documentary